Sistem Pakar Diagnosis Kerusakan Pada Komputer Menggunakan Metode Certainty Factor - DWI KURNIA DWI KURNIA (Journal of Information System and Artificial Intelligence, 2024)
Abstract. Computers have become an important part of various human work activities in this digital era. Along with the rapid development of technology. However, the use of hardware there is no age limit. there are still many ordinary people who have not been able to analyze computer damage. And it takes an expert to analyze computer damage, later the system will be created to help make it easier for an expert to analyze computer damage in an effective and efficient manner. The solution that will be used is to use an artificial intelligence approach. The way it works is by doing sophisticated reasoning so that it will diagnose expert system damage from symptom input. Certainty Factor (CF) is one of the techniques used to provide certainty over a fact. A desktop-based application that produces an "Expert System for Diagnosing Computer Damage Using Certainty Factor". The test results from consultation with this system indicate that the system is able to determine the damage based on the symptoms, as well as provide the percentage obtained from the Certainty Factor calculation process. Keywords: Expert System, Computer Damage, Certainty Factor